Phenotyping of Mice with Heart Specific Overexpression of A2A-Adenosine Receptors: Evidence for Cardioprotective Effects of A2A-Adenosine Receptors - Boknik, Peter; Drzewiecki, Katharina; Eskandar, John; Gergs, Ulrich; Grote-Wessels, Stephanie; Fabritz, Larissa; Kirchhof, Paulus; Müller, Frank U.; Stümpel, Frank; Schmitz, Wilhelm; Zimmermann, Norbert; Kirchhefer, Uwe; et al. (Frontiers in Pharmacology, 2018)
Background: Adenosine can be produced in the heart and acts on cardiac adenosine receptors. One of these receptors is the A2A-adenosine receptor (A2A-AR). Methods and Results: To better understand its role in cardiac function, we generated and characterized mice (A2A-TG) which overexpress the human A2A-AR in cardiomyocytes. In isolated atrial preparations from A2A-TG but not from WT, CGS 21680, an A2A-AR agonist, exerted positive inotropic and chronotropic effects. In ventricular preparations from A2A-TG but not WT, CGS 21680 increased the cAMP content and the phosphorylation state of phospholamban and of the inhibitory subunit of troponin in A2A-TG but not WT. Protein expression of phospholamban, SERCA, triadin, and junctin was unchanged in A2A-TG compared to WT. Protein expression of the α-subunit of the stimulatory G-protein was lower in A2A-TG than in WT but expression of the α-subunit of the inhibitory G-protein was higher in A2A-TG than in WT. While basal hemodynamic parameters like left intraventricular pressure and echocardiographic parameters like the systolic diameter of the interventricular septum were higher in A2A-TG than in WT, after β-adrenergic stimulation these differences disappeared. Interestingly, A2A-TG hearts sustained global ischemia better than WT. Conclusion: We have successfully generated transgenic mice with cardiospecific overexpression of a functional A2A-AR. This receptor is able to increase cardiac function per se and after receptor stimulation. It is speculated that this receptor may be useful to sustain contractility in failing human hearts and upon ischemia and reperfusion.